Polish Planners’ Attitudes Towards Citizen Participation - Damurski, Łukasz (Problemy Ekorozwoju, 2012)
In the Polish spatial-planning system, planners are situated between the citizens, developers, local authorities and non-governmental organizations. Such a unique position gives them an opportunity to promote and stimulate the cooperation between the most important local players in order to reach constant and sustainable development of a given territorial unit. A question arises here: how does citizen participation look in practice? This paper looks for the answer by presenting selected findings of a survey conducted with Polish planners in 2010. The results suggest that planners are aware of the need for public involvement in the planning process though they have some doubts about the real effects of such involvement. The planning practice proves that citizens first of all require satisfaction of their private interests, local authorities care mainly about the current political advantages and the planners lack the power and appropriate knowledge to conduct the public consultation process. The survey points to the need for improvement of the quality of the citizen participation in Poland.